2021
DOI: 10.1002/cctc.202100443
|View full text |Cite
|
Sign up to set email alerts
|

Highly Crystalline Post‐Consumer PET Waste Hydrolysis by Surface Displayed PETase Using a Bacterial Whole‐Cell Biocatalyst

Abstract: The enzymatic degradation of polyethylene terephthalate (PET) is a promising new approach for the environmentally friendly recycling of PET waste, but so far, low degradation rates paired with releatively high costs have limited the economic feasibility of this method. Here we present the construction of a new bacterial whole‐cell biocatalyst utilizing a new inverse autotranspoter based surface display of PETase in E. coli. The resulting catalyst allows an extremely easy production of large amounts of enzyme a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 52 publications
1
39
0
Order By: Relevance
“…Notably, a degradation efficiency reached 9.1% for highly crystalline PET (crystallinity > 20%) under the mild conditions at 30 °C used here, while a chemical method using more harsh conditions (100 vol % EtOH with 10 wt % NaOH at 50 °C) had PET degradation efficiency of 11.9% . There is still room for improvement of BIND-PETase compared with another study on enzymatic PET depolymerization (which reported 8% depolymerization at 25 °C in 3 days) . Collectively, our results demonstrated the applicability of the BIND-PETase biocatalyst in depolymerizing highly crystalline PET waste, which is promising for plastic recycling applications.…”
Section: Resultssupporting
confidence: 52%
“…Notably, a degradation efficiency reached 9.1% for highly crystalline PET (crystallinity > 20%) under the mild conditions at 30 °C used here, while a chemical method using more harsh conditions (100 vol % EtOH with 10 wt % NaOH at 50 °C) had PET degradation efficiency of 11.9% . There is still room for improvement of BIND-PETase compared with another study on enzymatic PET depolymerization (which reported 8% depolymerization at 25 °C in 3 days) . Collectively, our results demonstrated the applicability of the BIND-PETase biocatalyst in depolymerizing highly crystalline PET waste, which is promising for plastic recycling applications.…”
Section: Resultssupporting
confidence: 52%
“…This pH optimum is higher than the pH optima that have been determined for purified CHMOs, which were reported to be best active between pH 7 and 9 (Trudgill, 1990; Sheng et al ., 2001). Alterations in substrate specificities (Jose and von Schwichow, 2004) or turnover number (Schumacher et al ., 2012) by the surface display of enzymes have been reported before, as well as that surface displayed enzymes showed an altered pH optimum (Bussamara et al ., 2012; Gercke et al ., 2021). In addition, as shown by the example of cellulases, the same enzyme exhibited different pH optima when displayed on different host cells (Obeng et al ., 2018).…”
Section: Resultsmentioning
confidence: 99%
“…4A). The use of the YeeJ autotransporter translocation domain for the surface display of enzymes has been reported just recently (Gercke et al ., 2021). In consequence, a plasmid was constructed (pYeeJ‐ADH) encoding a YeeJ‐ADH autotransporter fusion protein.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations